Comparing the effect of three denture adhesives on the retention of mandibular complete dentures for diabetic patients (randomized clinical trial) - Ibraheem, E.M.A. (2021)
An in vivo clinical study is made of 30 male completely edentulous patients with low well-rounded mandibular ridges with an age group of 50–70 years were selected. All patients were controlled diabetic type 2. New complete dentures were constructed for them. The universal testing machine was used to measure forces required to dislodge the dentures. Retention of mandibular complete dentures was measured without adhesive and with the use of three types of denture adhesives after adaptation period of 1 month. A paste type (Fittydent) and two cream types (Protefix and Corega) were used. The average records after 15 min, 1 h, and 2 h were recorded. This study revealed that denture adhesives increase retention of complete dentures. Fittydent adhesive paste was more effective in improving the retention than Protefix and Corega adhesive creams. Therefore, denture adhesives improve patient satisfaction.